Putting participants and study partners FIRST when clinical trials end early. Issue 12 (2nd August 2022) - Largent, Emily A.; Walter, Sarah; Childs, Nancy; Dacks, Penny A.; Dodge, Shana; Florian, Hana; Jackson, Jonathan; Llibre Guerra, Jorge J.; Iturriaga, Erin; Miller, David S.; Moreno, Monica; Nosheny, Rachel L.; et al.
Abstract: Between 2018 and 2019, multiple clinical trials ended earlier than planned, resulting in calls to improve communication with and support for participants and their study partners ("dyads"). The multidisciplinary Participant Follow‐Up Improvement in Research Studies and Trials (Participant FIRST) Work Group met throughout 2021. Its goals were to identify best practices for communicating with and supporting dyads affected by early trial stoppage. The Participant FIRST Work Group identified 17 key recommendations spanning the pre‐trial, mid‐trial, and post‐trial periods. These focus on prospectively allocating sufficient resources for orderly closeout; developing dyad‐centered communication plans; helping dyads build and maintain support networks; and, if a trial stops, informing dyads rapidly. Participants and study partners invest time, effort, and hope in their research participation. The research community should take intentional steps toward better communicating with and supporting participants when clinical trials end early. The Participant FIRST recommendations are a practical guide for embarking on that journey.